2019
DOI: 10.1186/s12985-019-1222-9
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody-based capture ELISA in the diagnosis of previous dengue infection

Abstract: BackgroundDengue is an important mosquito-borne disease. There is currently only one licensed vaccine for dengue prevention. The vaccine provides higher efficacy in pre-vaccination dengue-seropositive persons but a higher risk of subsequent more severe dengue in dengue-seronegative persons. It is recommended that the dengue vaccine may be given in dengue-seropositive individuals or as mass vaccination without individual pre-vaccination screening in areas where the dengue seroprevalence is > 80% in children age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, it was labor- and resource-intensive and time-consuming. Its interpretation requires technical expertise and tends to be complicated, especially after the secondary infection [ 14 , 24 ]. Performing ELISA is much simpler and less resource-intensive than performing PRNT; however, most of ELISA platforms are in-house developed and in absence of standardized information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it was labor- and resource-intensive and time-consuming. Its interpretation requires technical expertise and tends to be complicated, especially after the secondary infection [ 14 , 24 ]. Performing ELISA is much simpler and less resource-intensive than performing PRNT; however, most of ELISA platforms are in-house developed and in absence of standardized information.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the fact that we used an in-house assay with limited validation [ 24 ], we demonstrated a high level of accuracy of IgG ELISA to determine DENV serostatus in serological evaluation. We recognize that the IgG ELISA used in this study was an in-house assay and is not available to be used in a non-research commercial setting for mass screening for pre-vaccination status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we obtained mAbs specific to HPeV3, which recognized sites 133–159 aa and the 275–280 aa site of VP0, which was not reported earlier. Moreover, we also developed an ELISA for detecting HPeV3 antigen using two of our newly generated HPeV3-specific mAbs (#8 and #39), as mAb-based ELISA is highly specific and sensitive towards viral antigen detection [ 35 ]. Our Octet assay suggested that both mAbs show a high binding affinity to the full-length HPeV3-VP0 recombinant protein.…”
Section: Discussionmentioning
confidence: 99%